Optimalisasi Aplikasi E-Learning Berbasis Moodle Untuk Pengembangan Dan Peningkatan Media Pembelajaran Secara Digital - Budi, Eko Setia; Priyatna, Ade; Zuraidah, Eva; Fadillah, Nur; Firmansyah, Ilhan; Rana, Dipo Yudhis; Fitriyani, Fitriyani; Roris, Renaldi Putra (Forum Kerjasama Pendidikan Tinggi, 2026)
Community Service is a routine activity carried out by lecturers of Higher Education in order to carry out the obligations of the Tridharma of Higher Education. Lecturers have an obligation to carry out the obligation to share knowledge and skills they have with the wider community who need help. One of the partners who needs support is Al Qomar School which currently has problems in the information system in the digital learning process. This often causes errors in the digital learning process. In addition, the partner also does not have a website application that can be used to display the school's digital learning that makes it easier for teachers to access digital learning quickly and efficiently. Based on this, this community service aims to provide Moodle-Based E-Learning Application Training for the Development and Improvement of Digital Learning Media at Al Qomar School that can be used by partners to improve learning performance better. The activity was carried out face-to-face at the Al Qomar School Hall, Jalan Kamal Raya No. 1 Kalideres, West Jakarta. The target output to be achieved in this activity is the publication of this training activity in national-scale electronic or print media. Improving the ability of the e-learning system aims to provide effective solutions in increasing learning flexibility, accommodating diverse learning styles, and facilitating learning accessibility. E-learning development using the Moodle platform, 100% of teachers are able to design learning with creative and innovative content